Omission of doxorubicin from the treatment of stage II–III, intermediate-risk Wilms' tumour (SIOP WT 2001): an open-label, non-inferiority, randomised controlled trial. Issue 9999 (19th September 2015) - Pritchard-Jones, Kathy; Bergeron, Christophe; de Camargo, Beatriz; van den Heuvel-Eibrink, Marry M; Acha, Tomas; Godzinski, Jan; Oldenburger, Foppe; Boccon-Gibod, Liliane; Leuschner, Ivo; Vujanic, Gordan; Sandstedt, Bengt; de Kraker, Jan; et al.
Summary: Background: Before this study started, the standard postoperative chemotherapy regimen for stage II–III Wilms' tumour pretreated with chemotherapy was to include doxorubicin. However, avoidance of doxorubicin-related cardiotoxicity effects is important to improve long-term outcomes for childhood cancers that have excellent prognosis. We aimed to assess whether doxorubicin can be omitted safely from chemotherapy for stage II–III, histological intermediate-risk Wilms' tumour when a newly defined high-risk blastemal subtype was excluded from randomisation. Methods: For this international, multicentre, open-label, non-inferiority, phase 3, randomised SIOP WT 2001 trial, we recruited children aged 6 months to 18 years at the time of diagnosis of a primary renal tumour from 251 hospitals in 26 countries who had received 4 weeks of preoperative chemotherapy with vincristine and actinomycin D. Children with stage II–III intermediate-risk Wilms' tumours assessed after delayed nephrectomy were randomly assigned (1:1) by a minimisation technique to receive vincristine 1·5 mg/m 2 at weeks 1–8, 11, 12, 14, 15, 17, 18, 20, 21, 23, 24, 26, and 27, plus actinomycin D 45 μg/kg every 3 weeks from week 2, either with five doses of doxorubicin 50 mg/m 2 given every 6 weeks from week 2 (standard treatment) or without doxorubicin (experimental treatment). The primary endpoint was non-inferiority of event-free survival at 2 years, analysed by intention to treat and a margin of 10%. Assessment of safety and adverse events included systematic monitoring of hepatic toxicity and cardiotoxicity. This trial is registered with EudraCT, number 2007-004591-39, and is closed to new participants. Findings: Between Nov 1, 2001, and Dec 16, 2009, we recruited 583 patients, 341 with stage II and 242 with stage III tumours, and randomly assigned 291 children to treatment including doxorubicin, and 292 children to treatment excluding doxorubicin. Median follow-up was 60·8 months (IQR 40·8–79·8). 2 year event-free survival was 92·6% (95% CI 89·6–95·7) for treatment including doxorubicin and 88·2% (84·5–92·1) for treatment excluding doxorubicin, a difference of 4·4% (95% CI 0·4–9·3) that did not exceed the predefined 10% margin. 5 year overall survival was 96·5% (94·3–98·8) for treatment including doxorubicin and 95·8% (93·3–98·4) for treatment excluding doxorubicin. Four children died from a treatment-related toxic effect; one (<1%) of 291 receiving treatment including doxorubicin died of sepsis, three (1%) of 292 receiving treatment excluding doxorubicin died of varicella, metabolic seizure, and sepsis during treatment for relapse. 17 patients (3%) had hepatic veno-occlusive disease. Cardiotoxic effects were reported in 15 (5%) of 291 children receiving treatment including doxorubicin. 12 children receiving treatment including doxorubicin, and ten children receiving treatment excluding doxorubicin, died, with the remaining deaths from tumour recurrence. Interpretation: Doxorubicin does not need to be included in treatment of stage II–III intermediate risk Wilms' tumour when the histological response to preoperative chemotherapy is incorporated into the risk stratification. Funding: See Acknowledgments for funders.